2008
DOI: 10.1029/2006wr005517
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X‐ray microtomography and interfacial partitioning tracer test measurements of NAPL‐water interfacial areas

Abstract: [1] Interfacial areas between an immiscible organic liquid (NAPL), and water were measured for two natural porous media using two methods, aqueous-phase interfacial partitioning tracer tests and synchrotron X-ray microtomography. The interfacial areas measured with the tracer tests were similar to previously reported values obtained with the method. The values were, however, significantly larger than those obtained from microtomography. Analysis of microtomography data collected before and after introduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
77
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 42 publications
12
77
1
Order By: Relevance
“…Analysis of the data sets indicated that REV requirements were met for image volumes of approximately 30–50 mm 3 (Figure 1). These results are similar to those reported in prior studies (Culligan et al, 2004; Brusseau et al, 2008). The volumes of the imaged zones were larger than the minimum for all data sets.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Analysis of the data sets indicated that REV requirements were met for image volumes of approximately 30–50 mm 3 (Figure 1). These results are similar to those reported in prior studies (Culligan et al, 2004; Brusseau et al, 2008). The volumes of the imaged zones were larger than the minimum for all data sets.…”
Section: Methodssupporting
confidence: 93%
“…The results of prior studies have shown that interfacial areas measured with the IPTT method are larger than values measured with microtomography (Brusseau et al, 2006, 2007, 2008). The observed disparity has been hypothesized to result from the impact of porous-medium surface roughness.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is critical to note that areas obtained with this method represent total areas, in that both capillary-associated and film-associated interfacial areas are included in the measurements. In addition, they incorporate interfacial area associated with microscopic surface roughness [Brusseau et al, 2006, 2007, 2008]. It is useful when comparing data for multiple porous media to normalize the measured A ia values by the specific solid surface area (s) measured using a method such as N 2 /BET.…”
Section: Methodsmentioning
confidence: 99%
“…While providing more spatial detail on NP transport, the 2D transport profile must still be inferred from the ten detector points (much of the column is still unseen). Gamma radiation and X-ray micortomography have been used for porous media characterization (Illangasekare et al 1995), fluid distribution (Brusseau et al 2008) and solute-fluid transport (Hofstee et al 1998) experiments. A major shortcoming of this method is at a single location; it requires relatively large counting times, leading to total counting times of several hours to produce an image (Werth et al 2010).…”
Section: Introductionmentioning
confidence: 99%